2005
DOI: 10.1016/j.joms.2004.07.019
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative report of patient problems and postoperative instructions

Abstract: Purpose-While surgery related stress may interfere with the patient's ability to concentrate on instructions, language difficulty or low health literacy may also impede appropriate doctor/patient communication. The purpose of this study is to understand from a sample of minority patients the types of problems encountered during healing and the level of information regarding elements of postoperative instructions they recalled receiving at an inner-city safety net hospital. We initiated a qualitative study to u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 13 publications
(14 reference statements)
1
25
0
3
Order By: Relevance
“…56 However, verbal education needs to be comprehensive and consistent with the written material. 11,19 The use of other education methods is lower 34,39 and this research also shows that the use of other educational equipment, such as videos, is not widespread, although previous studies have shown the positive effects of these on the effectiveness of education. Images, various concept maps, brochures and videos can promote the effectiveness of information and increase interest in the information.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…56 However, verbal education needs to be comprehensive and consistent with the written material. 11,19 The use of other education methods is lower 34,39 and this research also shows that the use of other educational equipment, such as videos, is not widespread, although previous studies have shown the positive effects of these on the effectiveness of education. Images, various concept maps, brochures and videos can promote the effectiveness of information and increase interest in the information.…”
Section: Discussionmentioning
confidence: 56%
“…28,38,39,50 However, it must be remembered that even though the hospital routinely provides education to all patients, not all remember receiving adequate instructions. 11 It may be that communication is not always meet between the healthcare staff and patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Language barriers encountered in the care of patients with limited English proficiency (LEP), a growing segment of the U.S. population 2 , adversely affect healthcare quality. Patients with LEP may have decreased access to acute care and preventive services [3][4][5][6] , decreased satisfaction with care 7,8 , poor understanding of instructions or medications 9,10 , longer hospital stays 11 , and an increased risk of medical errors and misdiagnoses [12][13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…They have been consistently shown to receive lower quality care than English-proficient patients on various measures: understanding of treatment plans and disease processes, satisfaction, and incidence of medical errors resulting in physical harm [2][3][4][5][6]. These disparities are rooted in obvious communication barriers but also may reflect cultural differences, clinician biases, and ineffective systems (i.e., structural barriers) [7].…”
Section: Linguistic Inequities In Health Care and The Moral Imperativementioning
confidence: 99%